The effect of role ambiguity and role conflict on job performance in the hotel industry: the mediating effect of job satisfaction - Unguren,Engin (2021)
Abstract Accommodation businesses are stressful workplaces due to their dynamic and demanding work environment. Role ambiguity and role conflict are major stress factors for hotel employees, causing low levels of satisfaction and performance and high levels of turnover. The main purpose of this study was to explore the mediating effect of job satisfaction on the relationship between role conflict, role ambiguity, and job performance. The data was collected through fully structured questionnaires from employees working in 3, 4 and 5 star hotels in Alanya, one of the leading tourism destinations in Turkey. The data was analyzed via structural equation modeling. The results revealed that both role conflict and role ambiguity have direct negative influences on job performance and job satisfaction for hotel employees. Moreover, it was also proved that job satisfaction mediates the effect of role conflict and role ambiguity on job performance. In line with the findings, theoretical and managerial implications, contributions, limitations, and future research directions were discussed. It was implied that role stress factors must be addressed seriously by hotel managers in order to increase job performance.